PERAN KONSELOR KELOMPOK BERDASARKAN PENDEKATAN ANALISIS TRANSAKSIONAL DALAM MEMBANTU KOMUNIKASI INTERPERSONAL - Alfi Rahmi; Neviyarni Neviyarni; Netrawati Netrawati (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Group leaders in group counseling have duties and roles that will assist in managing group activities. Based on the Transactional Analysis approach that the group leader has a role as protector, excuse, and operation as well as concentration. The transactional analysis approach can train group participants to have good interpersonal communication skills. The purpose of this study is to reveal the roles of group leaders in building interpersonal communication among group members through a transactional analysis approach. This type of research is a literature review. This literature review uses a qualitative approach with a descriptive analysis method. The reference sources are in the form of articles, books, and information from technology and communication media that are appropriate to the topics discussed. Through this literature review, the process of analysis, synthesis, summarizing, and comparing literature can be carried out with one. The results of the study reveal that interpersonal communication can be trained through a transactional analysis approach. This interpersonal communication includes the ability to listen to what is conveyed by other people, the ability to understand other people, the ability to communicate thoughts and feelings appropriately and clearly to others, the ability to accept and give mutual support to others, and the ability to solve conflicts when with other people. . To master these interpersonal communication skills, group counselors carry out structural analysis, transactional analysis, game analysis, and script analysis in the group counseling process. The counselor's ability to analyze will assist clients in building effective interpersonal communication